Different perspectives of prison guards and mental health workers in forensic care - Timar, Jasvant; Buurman, Evi; Westen, Koen; Delespaul, Philippe (Frontiers in Psychology, 2024)
Objectives This study investigates the differences in treatment perspectives of prison guards and mental health practitioners within a Psychiatric Prison Unit (PPU). Methods This qualitative study uses questionnaires and focus groups to explore the relationships between prison guards (N = 4) and mental health professionals (N = 6) working at the Psychiatric Prison Unit in Zwolle, the Netherlands. Two questionnaires (the Recovery Attitude Questionnaire and the Recovery Knowledge Inventory) were completed by the participants. A selected subsample based on diverging beliefs concerning treatment perspectives was recruited for additional focus groups. The dialogues were transcribed and coded into a comprehensive scheme. Responses were analyzed to describe perceptions and attitudes of respondents towards forensic care. Results This study identified three main themes: policy, communication, and person-dependent factors. Understaffing and high turnover rates in the correctional facility led to prioritization of safety concerns over treatment objectives. Guards and mental health professionals had different communication styles which hindered the alignment of treatment goals. Person-dependent factors, including personality traits and individual attributes, were significant in shaping collaborative interactions. Conclusion This study reveals agreement in the viewpoints between prison guards and mental health professionals but highlights the complex challenges in providing effective treatment within the confines of a correctional facility. These challenges are influenced by policy dynamics, communication limitations, and individual-specific factors.